A study on pacemaker pocket infection - Datta, Goutam (Journal of Cardiology and Cardiovascular Medicine, 2020)
Objective: Cardiac implantable electronic device (CIED) infections now constitute ∼ 10% of all endocarditis cases. The incidence of CIED infection is usually < 2%. Our objective was to study pacemaker pocket infection rate and different risk factors in our institution. Methods: This observational study was conducted over a period of five years from January 2011 to December 2016 and it included 1096 patients. Common risk factors like patients with diabetes, repeat procedure, chronic renal failure, chronic obstructive airway disease, immunosuppressive agents were studied in our patients. Results: Our study consisted of 1096 patients. Pacemaker pocket infection occurred in sixteen patients (1.5%). Chronic renal failure patients were one hundred thirty in our study (11.86%). There were three hundred fifty six diabetic patients (32.48%). Repeat procedure was done in ninety five patients (8.6%). Results: Our study consisted of 1096 patients. Pacemaker pocket infection occurred in sixteen patients (1.5%). Chronic renal failure patients were one hundred thirty in our study (11.86%). There were three hundred fifty six diabetic patients (32.48%). Repeat procedure was done in ninety five patients (8.6%) Eighty six patients were suffering from chronic obstructive airway (7.8%). Patients on immunosuppressive therapy were fourteen in our study (1.2%). Conclusion: Pacemaker pocket infections is a dreaded complication after pacemaker implantation. During implantation, there is a risk of device contamination with the patient’s own skin flora and it can be prevented by ideal surgical asepsis technique, pre and perioperative use of antibiotics.